2020
DOI: 10.1002/bmc.4942
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extraction and quantification technique for phenolics content of garlic (Allium sativum): An application for comparative phytochemical evaluation based on cultivar origin

Abstract: A range of conventional, i.e. maceration, percolation, ultrasonic assisted, Soxhlet and Soxtec extraction (STE), to advanced extraction techniques of accelerated solvent extraction (ASE) was utilized for the first time in order to optimize the extract yield and recovery of phenolics-gallic acid (GA), rutin (RT) and quercetin (QT)-quantified via ultra-high performance liquid chromatography with diode array detector (UHPLC-DAD). The effect of solvents (n-hexane, dichloromethane and methanol) and temperature (60,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Antioxidant activity depends on the position of phenol hydroxyl groups, and phenolic compounds with lower molecular weights exhibit their greater bioavailability [ 28 ]. The study of Ahmad et al [ 125 ] assessed the effect of methods, i.e., maceration, percolation, ultrasonic-assisted, Soxhlet and Soxtec extraction (STE), and accelerated solvent extraction (ASE), on the extract yield and phenolic content of Allium sativum L. In addition to the above, the effect of the type of solvents such as n-hexane, dichloromethane and methanol, and temperature (60, 80, and 100 °C) on the following factors such as extraction yield was evaluated, phenolic content and antioxidant activity (DPPH, and ABTS). Both STE and ASE methods using methanol as solvent at 100 °C showed high yield and recovery of the extract equal to 1221.10 mg/5 g (24.42%) and 91.50 mg/1 g (9.15%), respectively [ 125 ].…”
Section: Biological Properties Of Garlic Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidant activity depends on the position of phenol hydroxyl groups, and phenolic compounds with lower molecular weights exhibit their greater bioavailability [ 28 ]. The study of Ahmad et al [ 125 ] assessed the effect of methods, i.e., maceration, percolation, ultrasonic-assisted, Soxhlet and Soxtec extraction (STE), and accelerated solvent extraction (ASE), on the extract yield and phenolic content of Allium sativum L. In addition to the above, the effect of the type of solvents such as n-hexane, dichloromethane and methanol, and temperature (60, 80, and 100 °C) on the following factors such as extraction yield was evaluated, phenolic content and antioxidant activity (DPPH, and ABTS). Both STE and ASE methods using methanol as solvent at 100 °C showed high yield and recovery of the extract equal to 1221.10 mg/5 g (24.42%) and 91.50 mg/1 g (9.15%), respectively [ 125 ].…”
Section: Biological Properties Of Garlic Extractsmentioning
confidence: 99%
“…A positive correlation was found between the type of extraction, the yield of the extract, and the content of phenolic compounds, which was not the case between the antioxidant activity and the type of extraction for the STE method [ 125 ]. In the case of the ASE method, there was a positive correlation between the solvent and the extraction efficiency, phenols, and antioxidant activity, and no correlation was found between the extraction efficiency and DPPH activity.…”
Section: Biological Properties Of Garlic Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson et al [21] extracted total cannabidiol from cannabis by both maceration and percolation, respectively, and the results showed that percolation was more efficient than maceration extraction. In another study on the extraction of phenolics from Allium sativum, extraction and recovery rates were higher with percolation than with maceration [22]. Similarly, in a comparison of the extraction of volatile components from grapeseed oil, Soxhlet extraction yielded 67 volatile components, while percolation yielded 60 volatile components [23].…”
Section: Percolationmentioning
confidence: 94%
“…In general, factors such as powder size, solvent composition, extraction time, percolation flow rate, and solvent amount determine the efficacy of extraction [ 102 , 103 ]. In a study on phenolic extraction from Allium sativum L., percolation exhibited higher extraction and recovery rates than maceration [ 104 ]. Similarly, comparing volatile component extraction from grapeseed oil, percolation yielded 60 components, whereas Soxhlet extraction produced 67 [ 105 ].…”
Section: Approaches and Techniques For The Biodiscovery Of Anti-infla...mentioning
confidence: 99%